Survival, growth and reproductive performance in F1 crossbred cattle produced and managed on station in the Gambia - Diack, A.; Sanyang, F.B; Corr, N. (2004)
In a trial whereby a large number of cows were needed to calve at approximately the same time, opportunity was taken to establish a crossbred cow population at the International Trypanotolerance (ITC). A slight improvement in the traditional husbandry system revealed a great productivity potential of these crossbreds. Their survival rate to one year (i.e., 90.0%for the Jersey X N’Dama (J X N) and 71.2% for the Friesian X N’Dama was proved satisfactory in the local environment, though conclusions are that more attention is needed for rearing Friesian type F1 calves in the tropical environment. With an overall mean birth weight of 17.7±4.1 kg and an overall mean daily weight gain (DWG) of 0.220±0.104 kg they attained an average weight of 100.6±29.9 kg at one year. Their relatively retarded growth recommended a better management. Puberty was attained at 478.2±13.9 days, age at first calving 970.5±94.1 days and the overall mean calving interval and open period were 400±82.5 and 117±83.2 days, respectively.